Bio-inspired AIE pillar[5]arene probe with multiple binding sites to discriminate alkanediamines. Issue 97 (12th November 2021) - Zhou, Yibin; Tang, Hao; Li, Zhao-Hui; Xu, Linxian; Wang, Lingyun; Cao, Derong
Abstract : A pillar[5]arene functionalized with multiple binding sites can detect 1, 8-diaminooctane, 1, 10-diaminodecane, and 1, 12-diaminododecane selectively and sensitively by using the AIE mechanism and the induced-fit mechanism. Abstract : Two functionalized pillar[5]arenes (H1 and H2) with significant AIE properties were synthesized. H2 is an excellent probe to selectively detect specific alkanediamines owing to its multiple binding sites, which result in the enhancement of emission based on the AIE mechanism and the induced-fit mechanism, and provides a new strategy to develop probes with high selectivity and sensitivity.